1. Show using induction that
(1 + 1 / n + 1).(1 + 1 / n + 2). ... . (1 + 1 / n + n) = 2 - 1 / n + 1, n >= 1.

I've tried everything with this question but the right hand side is not the same as the left hand side after substituting k+1 in the place of n, please help.  Reply With Quote

2.

3. I have moved this topic, as it is a better fit with discrete mathematics than number theory.

I am assuming (given the lack of bracketing symbols) that you are given to prove:

$\displaystyle \prod_{j=1}^n\left(1+\frac{1}{n+j} \right)=2-\frac{1}{n+1}$ where $\displaystyle n\in\mathbb{N}$.

The first thing we wish to do is demonstrate the base case $\displaystyle P_1$ is true:

$\displaystyle \prod_{j=1}^1\left(1+\frac{1}{1+j} \right)=2-\frac{1}{1+1}$

$\displaystyle 1+\frac{1}{1+1}=2-\frac{1}{1+1}$

$\displaystyle \frac{3}{2}=\frac{3}{2}$

Thus, the base case is true.

Next, state the induction hypothesis $P_k$:

$\displaystyle \prod_{j=1}^k\left(1+\frac{1}{k+j} \right)=2-\frac{1}{k+1}$

Let's combine the two terms within the product:

$\displaystyle \prod_{j=1}^k\left(\frac{k+j+1}{k+j} \right)=2-\frac{1}{k+1}$

Let's pull out the first factor on the left.

$\displaystyle \frac{k+2}{k+1}\prod_{j=2}^k\left(\frac{k+j+1}{k+j} \right)=2-\frac{1}{k+1}$

This will allow us to re-index the product and replace $k$ with $k+1$:

$\displaystyle \frac{k+2}{k+1}\prod_{j=1}^{k-1}\left(\frac{(k+1)+j+1}{(k+1)+j} \right)=\frac{2k+1}{k+1}$

Next, multiply through by $\displaystyle \frac{k+1}{k+2}$:

$\displaystyle \prod_{j=1}^{k-1}\left(\frac{(k+1)+j+1}{(k+1)+j} \right)=\frac{2k+1}{(k+1)+1}$

Now, try as your induction step, multiplying by:

$\displaystyle \prod_{j=k}^{k+1}\left(\frac{(k+1)+j+1}{(k+1)+j} \right)=\frac{2(k+1)+1}{2k+1}$

What do you find?

Incidentally, there is an easier way to demonstrate the identity is true (if we hadn't been directed to use induction)...let's write the identity as:

$\displaystyle \prod_{j=1}^n\left(\frac{n+j+1}{n+j} \right)=2-\frac{1}{n+1}$

Now, we may choose to express this as:

$\displaystyle \frac{\prod\limits_{j=1}^n\left(n+j+1 \right)}{\prod\limits_{j=1}^n\left(n+j \right)}=2-\frac{1}{n+1}$

$\displaystyle \frac{\prod\limits_{j=2}^{n+1}\left(n+j \right)}{(n+1)\prod\limits_{j=2}^{n}\left(n+j \right)}=2-\frac{1}{n+1}$

$\displaystyle \frac{(n+(n+1))\prod\limits_{j=2}^{n}\left(n+j \right)}{(n+1)\prod\limits_{j=2}^{n}\left(n+j \right)}=2-\frac{1}{n+1}$

$\displaystyle \frac{2n+1}{n+1}=2-\frac{1}{n+1}$

$\displaystyle \frac{2(n+1)-1}{n+1}=2-\frac{1}{n+1}$

$\displaystyle 2-\frac{1}{n+1}=2-\frac{1}{n+1}$  Reply With Quote

The question did not include the product sign was why I couldn't figure it out, thank u so much for your help.  Reply With Quote

+ Reply to Thread induction, math, number theory #### Posting Permissions 